50 doa pilihan untuk anak : Mulai bangun tidur sampai tidur kembali / Muhammad Syafirin; Penyunting, Muhammad Ilham - MUHAMMAD Syafirin; MUHAMMAD Ilham (Idea Word Kidz, 2015)
52 hlm. : illus. ; 25 cm.